Peran Orang Tua dalam Mencegah Pernikahan Usia Dini - Afni Zuraidah Rangkuti; Ahmad Rivauzi (Prodi Pendidikan Keagamaan Islam, 2023)
Early marriage is a marriage carried out by a man and a woman or a couple who are under 19 years old or are currently attending high school. So a marriage is considered an early marriage, if both or one of the partners is under 18 years old (still in his teens). This research is a field research (Field Reaseach). is research that examines and analyzes a phenomenon, event, social action, or concept with the aim of arriving at a conclusion. Marriages in the Nelayan Village, Bilah Hilir District, and Labuhanbatu have been going on for a long time. The 2019 Marriage Law requires that couples who marry at an early age must be 19 years old. If the age does not reach 19 years, they must apply for a marriage dispensation, where a marriage dispensation is the granting of a right to someone who wants to marry but does not meet the minimum age limit set by the government. Early marriage occurs due to promiscuity, economy, lack of education and knowledge and lack of attention from parents in educating children. The lack of the role of parents in educating children causes many children to get married at an early age and seek attention from others.